Research on approaches to optimizing energy management in modern households - Shvetsova Svetlana (E3S Web of Conferences, 2023)
This article explores approaches to optimizing energy management in modern households. Energy expenditure in modern households is distributed across dozens of sources. Kitchen equipment and washing machines are among the main sources of energy consumption in households. Optimizing the operation of such equipment is one of the approaches to optimizing energy management in a modern household. Switching to less energy-intensive materials used in such equipment can help reduce energy consumption. The study explores the prospects for introducing such materials into laundry equipment. The obtained results of the analysis can be used in developing strategies by the marketing services of companies producing washing equipment, as well as by researchers in this field.